Identificación de microorganismos enteropatógenos en gallinas ponedoras ISA BROWN - Velásquez Velásquez, Eduardo Armando (2012)
SUMMARY One of the causes of death of the birds in the modern poultry is given by the incidence of Salmonella spp. The research was conducted at the farm site Bolívar Canton Syria Mocochal in the period from June to August 2012. It aimed to determine the presence of Salmonella spp. in water, food and eggs for human consumption, identify the types and subtypes of Salmonella spp and propose a strategy in handling biomedical laying hen farm. We evaluated two lots of 13,000 birds each 18 months of age and egg production. Samples of organs (liver, spleen, ovary, heart), water and food. For the identification of pathogens was used API 20-E. The results did not show the presence of Salmonella spp. in the organs tested, or in water or food, is achieved nevertheless identify the presence of the following pathogens: Proteus mirabilis, P. penneri, Enterobactercloacae organs and E.coli in liver and spleen. We proposed a biosecurity plan in handling farm type layers.